Advances in the Aetiophatogenesis of Sjögren’s Syndrome: a Literature Review - Pedro de Sousa Gomes; Gintaras Juodzbalys; Maria Helena Fernandes; Zygimantas Guobis (eJournal of Oral Maxillofacial Research, 2012)
Objectives: The purpose of present paper is to review and critically address the recent advances on the aetiopathogenesis of the Sjögren’s syndrome, taking into account the attained clinical features, with particular relevance given to the oral involvement. Material and Methods: A comprehensive review of the available literature between 1970 and 2012, regarding to the aetiopathogenesis and clinical findings related to Sjögren’s syndrome was conducted. Eligible studies were identified by searching the electronic literature PubMed, Medline, Embase, and ScienceDirect databases for relevant reports (last search update January 2012), combining the MESH heading term “Sjögren’s syndrome", with the words "salivary glands, xerostomia, xerophtalmia, aetiology". The authors checked the references of the selected articles to identify additional eligible publications and contacted the authors, if necessary. Results: This article addresses a large number of the recent advances in the aetiopathogenesis of the disease, taking into account the attained clinical features of both local and systemic nature. Detailed mechanisms of the hypothesized influence of viral infections, genetic and hormonal factors, and the relevance of the altered glandular homeostasis are critically discussed with particular relevance given to the local and systemic involvement of Sjögren’s syndrome. Conclusions: The increasing number of data published recently on the aetiophatogenesis of Sjögren’s syndrome strengthens the hypothesis that this condition, as all autoimmune diseases, is a multifactor disorder. Genetic predisposition, hormonal and environmental factors are thought to be implicated.